La vita come un romanzo. Esperienza religiosa e sproporzione narrativa partendo dalla riflessione di Paul Ricœur - Daniele Cananzi (Democrazia e Diritti Sociali)
The pages take up Paul Ricœur’s reflection with specific attention to the narrative dimension and religious experience in human existence. The two spheres of fallibility and disproportionality make it possible to provide a framework for the French philosopher’s contribution to the current human condition.